2017
DOI: 10.3389/fnbeh.2017.00239
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Total Sleep-Deprivation Impairs Contextual Fear Memory, and Contextual Fear-Conditioning Reduces REM Sleep in Moderately Anxious Swiss Mice

Abstract: The conditioning tasks have been widely used to model fear and anxiety and to study their association with sleep. Many reports suggest that sleep plays a vital role in the consolidation of fear memory. Studies have also demonstrated that fear-conditioning influences sleep differently in mice strains having a low or high anxiety level. It is, therefore, necessary to know, how sleep influences fear-conditioning and how fear-conditioning induces changes in sleep architecture in moderate anxious strains. We have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Because both learning and sleep alter hippocampal activity, intracellular signaling, and function ( 18 , 19 , 48 , 49 ), we next tested how cytosolic and MB ribosome-associated transcripts in different neuron types were affected by prior training on a hippocampus-dependent memory task. Consistent with previous findings from our laboratory and others’ ( 17 21 ), post-CFC SD disrupted CFM consolidation in the transgenic mice used in this study ( SI Appendix , Fig. S3 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Because both learning and sleep alter hippocampal activity, intracellular signaling, and function ( 18 , 19 , 48 , 49 ), we next tested how cytosolic and MB ribosome-associated transcripts in different neuron types were affected by prior training on a hippocampus-dependent memory task. Consistent with previous findings from our laboratory and others’ ( 17 21 ), post-CFC SD disrupted CFM consolidation in the transgenic mice used in this study ( SI Appendix , Fig. S3 ).…”
Section: Resultssupporting
confidence: 93%
“…Memory for this context-shock pairing is consolidated via hippocampus-dependent mechanisms over the next few hours ( 16 ). Critically, CFM consolidation can be disrupted by SD over the first 5 to 6 h following CFC ( 17 21 ). Over this same post-CFC interval, disruption of either neuronal activity ( 16 ), transcription ( 22 , 23 ), or translation ( 24 27 ) in the dorsal hippocampus can likewise disrupt consolidation.…”
mentioning
confidence: 99%
“…Sleep is divided into two distinct states: rapid eye movement (REM) sleep and non-rapid eye movement (NREM) sleep [ 5 , 7 ]. A study showed that changes in NREM sleep often correlate with anxiety levels in mice [ 8 ]. On the other hand, REM sleep latency is a feature of the early symptoms in depression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…REM-SD can cause a decline in memory and cognitive functions. Therefore, REM sleep plays a key role in learning and memory (4)(5)(6)(7). Neuroimaging is a powerful tool to explore the neural mechanism of sleep disorders.…”
Section: Introductionmentioning
confidence: 99%